The Influence of Operational Cost Budgets and Cost Control on Performance in Regional Drinking Water Companies (PDAM) - Sri Marliana; Arla Ainun Nasya; Irwan Sutirman Wahdiat (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines how budgeting operational costs and cost control affect the financial performance of PDAM. Industry of clean water that will be distributed to the community, good performance is needed. This performance assessment is useful for information in making decisions. This study uses a quantitative method, by distributing questionnaires to 45 employees from 3 PDAM companies, this study also uses linear regression analysis with the help of the SPSS application. Based on the results of the respondents' answers, it can be concluded that the operating cost budget has no impact on financial performance. However, what does have an impact on financial performance is cost control. Cost control allows the PDAM to improve service quality, and has a positive impact on long-term financial performance.